2016
DOI: 10.1186/s12917-016-0703-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs’ tolerability and safety – a systematic review and meta-analysis of adverse effects in dogs

Abstract: BackgroundThe safety profile of anti-epileptic drugs (AEDs) is an important consideration for the regulatory bodies, owners and prescribing clinicians. Information on their adverse effects still remains limited. A systematic review including a meta-analytic approach was designed to evaluate existing evidence for the safety profile of AEDs in canine patients. Electronic searches of PubMed, CAB Direct and Google scholar were carried out without date or language restrictions. Conference proceedings were also sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(142 citation statements)
references
References 101 publications
(247 reference statements)
4
137
0
1
Order By: Relevance
“…Since its introduction in 2013, imepitoin has become one of the two AEDs with the highest level of evidence for efficacy for the treatment of generalized tonic-clonic seizures, with an improved safety profile compared to phenobarbital [10, 11]. Imepitoin currently has no specific add-on therapy label for combination treatment with other AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in 2013, imepitoin has become one of the two AEDs with the highest level of evidence for efficacy for the treatment of generalized tonic-clonic seizures, with an improved safety profile compared to phenobarbital [10, 11]. Imepitoin currently has no specific add-on therapy label for combination treatment with other AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Imepitoin side effects were generally mild and short-lived, with a significant reduction in the number and severity of side effects observed after the initial 2 weeks of treatment. Ataxia, a common AED side effect [30] was mild or not present in the majority of cases, in line with recent objective evidence demonstrating reduced levels in IE patients treated with imepitoin compared to phenobarbitone [31]. A greater number of side effects were seen in dogs treated with imepitoin alongside other AEDs, which is in line with recent studies; for example, when imepitoin was used as an add-on therapy to phenobarbital, or vice versa, the number of side effects increased [32].…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital is a commonly used anti‐epileptic drug that has many known adverse reactions, both dose‐dependent and idiosyncratic. A recent systematic review of the safety of anti‐epileptics in dogs reported that over 50% of dogs receiving phenobarbital had an adverse reaction; however, these are usually mild and resolve with a lower dose or if the medication is withdrawn . The most commonly reported adverse reactions to phenobarbital are dose‐dependent (type 1) and include increased serum ALP and ALT activity, sedation, polydipsia/polyuria, ataxia, polyphagia, and chronic hepatopathy.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The most commonly reported adverse reactions to phenobarbital are dose‐dependent (type 1) and include increased serum ALP and ALT activity, sedation, polydipsia/polyuria, ataxia, polyphagia, and chronic hepatopathy. Reported idiosyncratic (type 2) reactions to phenobarbital are much less common and include blood dyscrasias, pancreatitis, necrolytic dermatitis, and dyskinesia . Due to the rare occurrence of these idiosyncratic reactions, they might go unrecognized for long periods of time.…”
Section: Acknowledgmentsmentioning
confidence: 99%